Seismic features and origin of fluid escape pipes offshore Hainan Island on the northern slope of South China Sea. (November 2021) - Chen, Duanxin; Zhang, Guangxu; Wang, Xiujuan; Wang, Zhenzhen; Chen, Shanshan; Dong, Dongdong
Abstract: Fluid escape pipes form when subsurface fluids flow upwards. Various factors can lead to their occurrences. Here we present an example offshore Hainan Island in the northern South China Sea (SCS) where buried mass transport deposits (MTDs) played an important role in the formation of fluid escape pipes. Based on a three dimensional (3D) seismic reflection dataset, more than 120 seismic pipes seemed to be distributed irregularly in the shallow 230 m sequences over an area of 150 km 2 . The pipe field seats on a gentle slope segment that is nipped by steep and rugged slope where abundant seabed MTDs exist. The pipes can be divided into two types; ones terminate upward at the seabed with pockmarks and the others have upper extremes vanishing at levels 20–85 m below the seabed. Pipes are deduced to form due to escapes of overpressured fluid indicated by stacked high amplitude reflections (HARs) at lower part of pipes and below pipes. MTDs are observed to have a well correspondence with buried MTDs, and their couples are grouped into four relatively independent regions that are separated by normal sequences. It is suggested that these buried MTDs triggered the release of overpressured fluid due to differential compaction between MTDs bodies and overlying/lateral sediment. Buried MTDs eventually determined the spatial distribution, shape, and scale of fluid escape pipes. Selective occurrences of pipes on the gentle slope rather than the steep slope depended on the sedimentary setting, in which the undisturbed clinoform was well developed overlying widespread MTDs in late Quaternary on the gentle slope, but was absent on the steep slope. This leaded to a process of rapid deposition to favor the formation of overpressured fluid compartment at/near pipe roots on the gentle slope. Moreover, this work provided significant results for the oil company to avoid the pipeline route crossing the pipe field, even if it has a gentler terrain. Highlights: Multitudes of fluid pipes on slope of SCS threaten seabed engineering. The occurrence of fluid escape pipes was related to buried MTDs. Different shelf-slope systems can build up overpressure or destroy it.